Can somebody show me the steps to prove this question. Prove that: cos x + cos x = 2sec x 1 - sin x 1 + sin x
Follow Math Help Forum on Facebook and Google+
{cosx}/{1-sinx} + {cosx}/{1+sinx} = {(cosx)(1+sinx)+(cosx)(1-sinx)}/{(1-sinx)(1+sinx)}= ={(cosx)(1+sinx)+(cosx)(1-sinx)}/{(1-(sinx)^2}= ={(cosx)(1+sinx)+(cosx)(1-sinx)}/{(cosx)^2}= ={(1+sinx)+(1-sinx)}/{(cosx)}= ={2}/{cosx}= =2secx
Originally Posted by GAVREED2 Can somebody show me the steps to prove this question. Prove that: cos x + cos x = 2sec x 1 - sin x 1 + sin x working on the left side, get a common denominator ... ... then add the two fractions.
View Tag Cloud